Vytápění penzionu - Kubík, Michael (Vysoké učení technické v Brně. Fakulta stavební, 2022)
Hlavním předmětem této bakalářské práce je návrh vytápění penzionu, který se nachází v horské oblasti. Práce je rozdělená na 3 hlavní části – teoretickou, výpočtovou a projekt. V teoretické části je představena biomasa a také petely. Výpočtová část je zaměřena na konkrétní návrh vytápění ohřevu a teplé vody. V poslední části práce je k dispozici technická zpráva a projekt objektu.

The main subject of this bachelor thesis is the design of a heating system for a guesthouse located in a mountain area. The thesis is divided into 3 main parts - theoretical, computational and project. In the theoretical part, biomass and also petels are introduced. The second main part is focused on the concrete design of the heating system for heating and hot water. In the last part of the thesis, the technical report and the design of the building are provided.
Heating of the guesthouse
Keywords: Vytápění; penzion; horská oblast; biomasa; pelety; tepelná ztráta; příprava teplé vody; kotel na pelety; otopné těleso; otopná soustava; solární soustava.; Heating; guesthouse; mountain area; biomass; pellets; heat loss; hot water preparation; pellet boiler; heating element; heating system; solar system.